New High School in Santa Catarina: curricular organization, implications and formative meanings (PerCursos, 2022)
With the approval of the new Secondary Education Law (Law 13.415/17), and the National Common Curriculum Base for Secondary Education (BNCC), in 2018, federative entities found themselves compelled to build or reformulate their curricula and pedagogical proposals for this purpose. stage of Basic Education. In Santa Catarina, this process of implementing the New High School (NEM) in the state public network took place through the document entitled Base Curriculum of the Santa Catarina High School Territory (CBTCEM). Thus, based on documental and bibliographic analysis, the objective of this text is to analyze the New High School in Santa Catarina's public school system and its possible implications for youth training processes. The Santa Catarina NEM is composed of the Basic General Training, which is aligned with the BNCC, and the Flexible Part, which is composed of a Life Project, Second Foreign Language, Elective Curriculum Components and Deepening Paths. In addition to this new structure, other changes involve the expansion of the workload, the possibility of partnership with other institutions (including business) and distance activities, interdisciplinary pedagogical work based on skills and abilities and technical and professional training. A priori, it is possible to infer that the changes made to the high school curriculum, although they may be attractive, are in line with the recommendations of multilateral international organizations, which may limit access to general knowledge and direct the training of youth to pragmatic and meritocratic biases.
Keywords: high school reform; Santa Catarina; base curriculum of the Santa Catarina territory